Hydrodynamics and Heat Transfer Characteristics of a Double Gradient Microchannel Porous Model: Fixed Gradients and Variable Gradients Structures. Issue 4 (13th February 2020) - Chen, Xiangyang; Liu, Jie; Fan, Yanbin
Abstract: Hydrogen production from fluid fuel catalytic reaction is currently a hot research topic and catalyst carriers are the core of the hydrogen production process. The relationship between variable gradient structure and fixed gradient structure is still unclear. The hydrodynamics and heat transfer characteristics of double gradient and fixed gradient microchannel porous models are investigated. A strategy of using a uniform interpolation method to investigate the laws of a continuity equation is developed. There are three major findings. First, the internal fluid velocity of the variable gradient model is greater than the internal fluid velocity of the fixed gradient model. Second, the overall temperature change of the variable gradient structure is greater than the temperature change of the control group. Third, the formula of the macroscopic average temperature change of the area‐based fluid is found to be theoretically reliable. These findings may contribute to improving the catalytic efficiency of microchannel porous catalytic supports. Abstract : The hydrodynamics and heat transfer characteristics of double gradient and fixed gradient microchannel porous models are investigated. A strategy of using a uniform interpolation method to investigate the laws of a continuity equation is developed and a formula of the macroscopic average temperature change of the area‐based fluid is found to be theoretically reliable.